DEVELOPMENT OF BIOTECHNOLOGY LEARNING TOOLS BY UTILIZING THE LOCAL POTENTIAL OF CAMPEDAK SKIN TO IMPROVE THE SCIENCE PROCESSING SKILLS OF CLASS XII STUDENTS AT MA SABILARRASYAD SAMARINDA - Patang, Nurfadilah A.; Masswaet, Elsje Theodora; Palenewen, Evie; Hudiyono, Yusak; Tarigan, Daniel; Susilo, susilo (Universitas Tanjungpura, 2024)
ABSTRACTThis research aimed to produce Biotechnology learning tools by utilizing the local potential of cempedak peel to improve the science process skills of class XII students and determine its validity and effectiveness. This is development research that refers to Borg Gall